Diagnóstico da atividade pesqueira do Arquipélago de Fernando de Noronha/PE: sugestões para o manejo - Zeineddine, Gabriela Campos (2024)
Artisanal fishing exerts significant influence in several locations in Brazil, including the Northeast and the Archipelago of Fernando de Noronha-PE. Despite the worldwide social and economic importance of fishing being imminent, this activity is also a major source of disturbances in the marine environment, making fisheries management and planning actions essential for resource conservation and activity sustainability. Due to the lack of existing data regarding fishing categories developed in Fernando de Noronha, as well as current fishing statistics that support its planning, this work aims to diagnose current fishing practices and suggest management alternatives based on the local fishing reality, with ways to make conservation and local fisheries management compatible. The data for this research were collected within the scope of fishing management carried out by ICMBio Noronha through fishing monitoring, fishing monitoring plans, and participatory fishing diagnosis meetings held with the management body and the local community. Currently, there are 94 fishermen in Fernando de Noronha, of which 35 carry out fishing activities on the beaches and 59 on boats. The fishing fleet is composed of 46 vessels, of which 27 carry out fishing activities, fishing tourism, and tours, and 19 are exclusively for fishing. Local fishing activity falls into three fishing categories: professional fishing, subsistence fishing, and amateur fishing. There is also fishing tourism, a tourist activity that interfaces between professional and amateur fishing. Despite the fishing fleet being small and fishing being restrictive in terms of richness, it was possible to observe seasonal patterns in catches, with autumn being the most productive season due to climatic factors. The geographical issues of fishing spots also have a direct influence on the composition and abundance of fishing production, demonstrating different behaviors for small and medium-sized vessels, which occupy spaces more or less distant from the island of Fernando de Noronha. The main current social need is the valorization of traditional fishing and the reestablishment of its pillars, such as strengthening the fishing class, unity among fishermen, and incentives for awareness programs and appreciation of fish and traditional culture, as well as active participation of the fishing community in management decision making. This study is expected to support decision-making for island fisheries management, as well as new research related to the topic.